Kesenian Singa Manuk dari desa Anggasari Kabupaten Subang (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
This study aims to describe the dynamics of the development of the Singa Manuk art in the village of Anggasari, Subang Regency, from 2003-2015. The author uses historical methods, namely heuristics, criticism, interpretation, and historiography. The research technique uses field studies and literature studies. Based on the results of the study, it was explained that the background of the birth of Singa Manuk art in Anggasari Village was due to a cultural mix between Subang culture through its Sisingaan art and typical Pantura’s dangdut music which was based on the unrest of the artists in Anggasari Village about the dimming of the artistry so that it gave birth to innovations namely Singa Manuk art. Singa Manuk art experienced a dynamic development from 2003 by Sanggar Genades until 2015. Singa Manuk art in Anggasari Village is experiencing continuous development and innovation by artists in the village so that Singa Manuk art continues to be in demand by the community and is preserved. The effort to preserve the Singa Manuk art involves various parties, namely artists, district governments, village governments, and the community who preserve Singa Manuk art.
Keywords: Art Preservation; Singa Manuk Art; Subang Art